Association of a genetic variant in the AKT gene locus and cardiovascular risk factors - Kermanshahi, Farnoush; Ghazizadeh, Hamideh; Hussein, Nasih Abdulla; Amerizadeh, Forouzan; Samadi, Sara; Tayefi, Maryam; Kamel Khodabandeh, Atiyeh; Moohebati, Mohsen; Ebrahimi, Mahmoud; Esmaily, Habibollah; Sahebi, Reza; Abdulkarimi, Rahim; et al. (Cellular and Molecular Biology, 2020)
Cardiovascular disease (CVDs) is the leading cause of morbidity and death worldwide. Most genetic variants could be identified by several genome-wide-association-studies (GWAS), including within genes encoding proteins involved in the AKT/PI3K pathways that are related with an increased risk of metabolic syndrome and CVDs. Therefore, due to the importance of genetic variants in the prognosis of diseases, we examined the genetic polymorphism of AKT-rs1130233 located on chromosome 14 with cardiovascular risk factors. In this cross-sectional study, 721 subjects recruited from the Mashhad-Stroke and Heart-Atherosclerotic-Disorders (MASHAD) cohort study. The participants including 257 subjects with metabolic syndrome, 144 subjects with cardiovascular disease and 320 subjects as a control group. Anthropometric, biochemical and demographic information measures were prepared. Dietary assessment was managed by 24h dietary recall. DNA extraction and genotyping were carried out by using the TaqMan real-time-PCR based method. The association of AKT rs1130233 locus with dietary intakes, metabolic syndrome and cardiovascular risk factors were assessed. Data were analyzed by using SPSS 21 software. Frequencies of genotypes AA, AG and GG of the AKT rs1130233 polymorphism were 12.6%, 44.5% and 42.9% in subjects with metabolic syndrome and 9.7%, 39.6% and 50.7% in subjects with cardiovascular disease, respectively. The frequency of allele A and G in cardiovascular disease and metabolic syndrome population were 29.5%, 70.5% and 34.8%, 65.2%, respectively. We have found no significant association between the AKT rs1130233 polymorphism with cardiovascular risk factors and metabolic syndrome. The results of dietary intake showed that the levels of phosphorus intake (p=0.008), calcium intake (p=0.007) and iodine intake (p=0.04) were different in subjects with and without metabolic syndrome. And also, energy intake was significantly different in subjects with cardiovascular disease (p=0.01) compared to the control group. Our findings suggest that AKT rs1130233 was not associated with the risk of metabolic syndrome and cardiovascular disease in the Iranian population. More studies are needed to validate our results. We did functional analysis, due to certify our investigation about value of this genetic biomarker for CVD risk.